Pregled raziskav o izbranih člankih na Wikipediji - Noč, Manca (Knjižnica, 2012)
The article represents an overview of relevant Wikipedia studies, especialiy those concerning featured articles. Featured artides are those that rank among the best articles according to Wikipedia's editors and should adhere both to Wikipedia's guidelines and rules and ali specific criteria for featured articles. Studies ofWikipedia's featured artlcles are significant because they show their characteristics. The use of Wikipedia is growing among high school and university students who often (uncriticaliy) summarize the Wikipedia content without verifying the accuracy of the information or checking for further sources.
Keywords: izbrani članki; pregled raziskav; slovenska Wikipedija